Identifikasi Kesulitan Membaca Pemahaman Mahasiswa - Ni Wayan Monik Rismadewi (Jurnal Bimbingan dan Konseling Indonesia, 2023)
This study intends to identify and particularly explain the reading comprehension difficulties faced by students in MPK English classrooms. This study employs a qualitative descriptive design in order to achieve its objectives. This study’s subjects, a total of 63 students, were chosen by using probability sampling from multiple classes of MPK English classes using simple random sampling. Interviews and survey (questionnaire) methods are used to obtain the data. Unstructured interviews were conducted with 10 students who were chosen from a total of 63 participants. Questionnaires were distributed online in the form of a Google form and completed by all subjects. The collected data were analyzed using the Interactive Analysis model which consisted of several stages, namely data collection, data reduction, data display, and conclusions. Based on the data analysis, it was found that of the five components of reading difficulties in reading comprehension of English texts, students found difficulties in terms of: a) finding the main idea, b) understanding vocabulary, and c) making inferences. Whereas in the other two components, namely finding references and finding specific information, there were no significant challenges. Abstrak: Penelitian ini bermaksud untuk mengidentifikasi dan secara khusus menjelaskan kesulitan membaca pemahaman yang dihadapi oleh siswa di kelas Bahasa Inggris MPK. Penelitian ini menggunakan desain deskriptif kualitatif untuk mencapai tujuannya. Subyek penelitian ini, sebanyak 63 siswa, dipilih dengan menggunakan probability sampling dari beberapa kelas bahasa Inggris MPK menggunakan simple random sampling. Metode wawancara dan survei (kuesioner) digunakan untuk memperoleh data. Wawancara tidak terstruktur dilakukan terhadap 10 mahasiswa yang terpilih dari total 63 partisipan. Kuesioner disebar secara online dalam bentuk Google form dan diisi oleh semua subjek. Data yang terkumpul dianalisis dengan menggunakan model Analisis Interaktif yang terdiri dari beberapa tahapan yaitu pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan analisis data, ditemukan bahwa dari lima komponen kesulitan membaca pemahaman membaca teks bahasa Inggris, siswa mengalami kesulitan dalam hal: a) menemukan gagasan utama, b) memahami kosa kata, dan c) membuat kesimpulan. Sedangkan pada dua komponen lainnya yaitu pencarian referensi dan pencarian informasi spesifik tidak terdapat kendala yang berarti.